PERANCANGAN ALGORITMA PENJADWALAN PEMBUATAN CETAKAN SESUAI DENGAN DUE DATE JADWAL PELEBURAN LOGAM UNTUK MENDUKUNG KONSEP SISTEM PRODUKSI TERDISTRIBUSI MANDIRI ( STUDI KASUS SEKSI FOUNDRY PT. BANINUSA INDONESIA ) - Martawirya, Yatna Yuwana; Arthaya, Bagus; Yanni, Yanni (Mesin, 2002)
At this moment, manufacturing industries in Indonesia must have high flexibility that can quickly responds dynamic changes in production processes. Autonomous Distributed Manufacturing System (ADiMS) is one of the production system alternative that can increase system flexibility with ability to adapt dynamic changing condition in the system.ADiMS is a production system where productions elements are independent, which planning process and production control is distributed to each independent element. Each of productionâs element has autonomy in running the monitoring, taking the decision, controlling, and communications functions with the other productionâs elements. Because each of the production elements take the decision independently, there should be a coordination of decision making result so the conflict will not occur among independent production elements.In this research AdiMS concept is applied in Foundry section at PT. Baninusa Indonesia. The task is to make a sand mold producing schedule based on the schedule of melting of cast iron or cast steel so it can support castâs order and filling the customer order. This research is done with the help of application program that specialized developed so it is hoped will make results a better scheduling of making sand mold casting.